Phase 1 study of inotuzumab ozogamicin combined with R-GDP for the treatment of patients with relapsed/refractory CD22+ B-cell non-Hodgkin lymphoma. (1st January 2017) - Sangha, Randeep; Davies, Andrew; Dang, Nam H.; Ogura, Michinori; MacDonald, David A.; Ananthakrishnan, Revathi; Paccagnella, M. Luisa; Vandendries, Erik; Boni, Joseph; Goh, Yeow Tee
Abstract: Objective : To evaluate safety, tolerability, and preliminary activity of inotuzumab ozogamicin (InO) plus rituximab, gemcitabine, dexamethasone, and cisplatin (R-GDP) in patients with relapsed/refractory CD22+ B-cell non-Hodgkin lymphoma (NHL). Methods : Patients received InO plus R-GDP (21-day cycle; six-cycle maximum) using up-and-down dose-escalation schema for gemcitabine and cisplatin to define the highest dosage regimen(s) with acceptable toxicity (Part 1; n = 27). Part 2 ( n = 10) confirmed safety and tolerability; Part 3 ( n = 18) evaluated preliminary efficacy. Results: Among 55 patients enrolled, 42% were refractory at baseline (median 2 [range, 1–6] prior therapies); 38% had diffuse large B-cell lymphoma (DLBCL). The highest dosage regimen with acceptable toxicity was InO 0.8 mg/m 2, rituximab 375 mg/m 2, cisplatin 50 mg/m 2, gemcitabine 500 mg/m 2 (day 1 only) and dexamethasone 40 mg (days 1–4); this was confirmed in Part 2, in which three patients had dose-limiting toxicities (grade 4 thrombocytopenia [ n = 2], febrile neutropenia [ n = 2]). Most frequent treatment-related adverse events were thrombocytopenia (any grade, 85%; grade ≥3, 75%) and neutropenia (69%; 62%). Overall (objective) response rate (ORR) was 53% (11 complete, 18 partial responses); ORR was 71%, 33%, and 62% in patients with follicular lymphoma ( n = 14), DLBCL ( n = 21), and mantle cell lymphoma ( n = 13), respectively. Conclusions: InO 0.8 mg/m 2 plus R-GDP was associated with manageable toxicity, although gemcitabine and cisplatin doses were lower than in the standard R-GDP regimen due to hematologic toxicity. Evidence of antitumor activity was observed; however, these exploratory data should be interpreted with caution due to the small sample size and short follow-up duration (Clinicaltrials.gov number: NCT01055496).